Gastos ambientais, fatores explicativos nos municípios da região oeste e sudoeste do Paraná - Paris, Dilce Simões dos Santos (2022)
Population growth and the consequent increase in consumption have been fostering the discussion on sustainable development as a way of preserving the planet, and it has gained notoriety mainly in regard to environmental degradation. This scenario is driving public managers to plan actions toward environmental preservation. An important milestone in this sense was the adherence to the goals of the 2030 Agenda for Sustainable Development. In this context, this study’s objective was to identify the explanatory factors for the volume of resources related to the environment applied in the municipalities of the western and southwestern Paraná. The method used was data collection with a qualitative and quantitative approach and analysis of the variables studied in the research problem. The research was developed as an empirical study through data collection directly and/or indirectly through the internet on the pages of the municipalities from the sample. The Multivariate Data Analysis technique was employed through multiple linear regression in order to explain the relationship between the selected variables. As a result, using 18 of the Multi-year Plans as a basis function, it was possible to identify that some municipalities have a greater commitment to the environment than others regarding the percentage of resources invested in environmental actions. The results also indicate that there is a connection between population size and the basic education index as explanatory factors for a greater allocation of resources to the environment, when compared to the total expenditure of each municipality.